Functional redundancy of necrotrophic effectors – consequences for exploitation for breeding - Tan, Kar-Chun; Phan, Huyen T. T.; Rybak, Kasia; John, Evan; Chooi, Yit H.; Solomon, Peter S.; Oliver, Richard P. (Frontiers in Plant Science, 2015)
Necrotrophic diseases of wheat cause major losses in most wheat growing areas of world. Breeding for disease resistance to tan spot and Septoria nodorum blotch is compromised by the universal finding that resistance was quantitative and governed by multiple quantitative trait loci (QTL). Most QTL had a limited effect that was hard to measure precisely and varied significantly from site to site and season to season. The discovery of necrotrophic effectors has given breeding for disease resistance new methods and tools. For P. nodorum, three effectors SnToxA, SnTox1 and SnTox3, have been well characterised. Unlike tan spot, no one effector has a dominating role. Genetic analysis of various mapping populations and pathogen isolates has shown that different effectors have varying impact and that epistatic interactions also occur. As a result the deployment of these effectors for SNB breeding is more complex. We have deleted the three effectors in a strain of P. nodorum and measured effector activity and disease potential of the triple knockout mutant. The culture filtrate causes necrosis in several cultivars and the strain causes disease, albeit the overall levels are less than in the wild type. Modelling of the field disease resistance scores of cultivars from their reactions to the microbially-expressed effectors SnToxA, SnTox1 and SnTox3 is significantly improved by including the response to the triple knockout mutant culture filtrate. This indicates that one or more further effectors are secreted into the culture filtrate. We conclude that the in vitro-secreted necrotrophic effectors explain a very large part of the disease response of wheat germplasm and that this method of resistance breeding promises to further reduce the impact of these globally significant diseases.